Optimization of Traffic Police Public Education by Security and Safety Unit for Preventing Traffic Accidents in the Area of Resort Police Semarang - Adho Ridwan (Advances in Police Science Research Journal, 2024)
The high number of traffic accidents in Semarang City indicates the lack of knowledge and awareness of the public in traffic. The research focus in this final project is on the optimization of Dikmas Lantas (community education in traffic) by the Kamsel (security and safety) Unit in preventing traffic accidents in the Semarang Police area. This research is considered important because traffic accidents over the past five years in Semarang City have been high. Therefore, the Kamsel Unit of Semarang Police tries to optimize Dikmas Lantas so that the number of traffic accidents in the Semarang Police area decreases. This research aims to describe: (1) How the Organizational Resources of the Kamsel Unit of the Semarang Police Traffic Unit and (2) Describe the efforts to optimize the Dikmas Lantas by the Kamsel Unit in preventing traffic accidents in the Semarang Police area. The author uses a qualitative approach, field research method and data collection techniques with interviews, observations, and document reviews. The author uses the concept of optimization, the concept of community service, the concept of the concept of the Kamsel unit. The concept of traffic accidents, the concept of traffic lighting, POAC theory, 5M theory, communication theory and SWOT theory. The results showed that the dikmas lantas carried out was not optimal due to the lack of quality and quantity of Kamsel Unit human resources, limited budget owned, planning the sequence of steps and actions and determining poor communication channels, uneven division of tasks, lack of direct delivery in the implementation of dikmas lantas, and lack of making hard copies in each activity report. Therefore, the problem solving efforts are, providing training, managing the budget properly, planning in accordance with the Chief of Police’s Guidelines, determining the appropriate channel according to the conditions of the situation, distributing tasks equally, direct socialization is intensified, and making hard copies to facilitate future leadership evaluation.